PENGARUH PEMBELAJARAH KOOPERATIF TIPE JIGSAW TERHADAP HASIL BELAJAR SISWA MI AL HAKIM - Dian Nurlaila; Iqnatia Alfiansyah; Nataria Wahyuning Subayani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Education is a process used to develop students' potential in improving knowledge and skills. MI Al Hakim is a school under the auspices of the Al Hakim foundation. The problems at MI Al Hakim include a relatively low level of learning completeness and low student motivation. Therefore, this study aims to apply the jigsaw type cooperative learning model to students' learning outcomes. This research uses experimental research with a pretest-posttest design. The results of the study show that the jigsaw type cooperative learning has a significant effect on the learning outcomes of MI Al Hakim students. Students' scores increased significantly and reached learning completeness. From the results of the study, it is concluded that the jigsaw type cooperative learning is effective for students' learning outcomes.